O ZONEAMENTO ECOLÓGICO-ECONÔMICO COMO INSTRUMENTO POLÍTICO DE PLANEJAMENTO E COMO INSTRUMENTO JURÍDICO: SUA DIMENSÃO POLÍTICA E REGULATÓRIA À LUZ DA ANÁLISE DA COMPREENSÃO DOS ATORES NO ESTADO DE MATO GROSSO DO SUL - Lima, Carolina Albuquerque (2008)
Mato Grosso do Sul State is becoming the scenario of the expansion of sugarcane crops for ethanol production. Since 2000, sugarcane is being expanded over the cerrado and the high pantanal, covering 37 out of the State s 78 municipalities, being Rio Brilhante, Maracaju, and Sonora the greatest producers nowadays. There is a conflict between the fostering of sugarcane planting and the installation of alcohol plants, which is yielding the country devises that reached 8% of its GDP in 2006, around R$ 2.3 trillion, and the preservation of the ecosystems which, among other important functions, support the water system. To conciliate such opposite objectives, the country has, since 2002, the Ecological-Economic Zoning (ZEE) instrument. At this moment, there is a series of debates about the creation of the ZEE in the area of sugarcane production in order to defend the ecosystems without forsaking wealth production. The ZEE-MS is still an ongoing process; because of this, we abandoned the initial objective of examining its effectiveness and changed our focus to the construction of the process itself, to the detailment of this context through the speech of its agents: we identify who talks, who debates, what is put forward and what are the interests involved. We analyze in this study the ongoing debates on the construction of the ZEE-MS while instrument of sustainable development. In order to accomplish this, it is utilized, in this work, the analysis of the discourse, with the objective of comprehending the context and identifying the political, social, and economic influence in the formation of this politico-legal-environmental instrument. We especially utilized the analysis of the interdiscourse, which comprehends the analysis of the conditions of production of the discourse and also the social-politico-ideological context of the subject who produced that discourse. In this way, we investigate whether the rules concerning the development of the ZEE-MS are being observed or not, a task of the utmost importance as this institution has a major role in solving or preventing the existing conflicts between those different social actors.